Knowledge creation and transfer in a global professional advisory firm - Law, Wayne Kok Kheng. (2008)
The main purpose of this study is to explore the knowledge creation and transfer activities, and the cultural enablers in the Singapore practice of a global professional advisory firm, BigFive, where the author is currently employed. At the time of writing, BigFive is in the process of implementing a global knowledge management system. Hence, the worldwide implementation of a global knowledge management represents a window of opportunity to study knowledge management in global organisation from a local (Asian) perspective.